NORSE ASSOCIATED WITH ANTI-GLYCINE RECEPTOR ANTIBODIES. Issue 12 (15th November 2016) - Robinson, Ruth; Hughes, Rod; Fowle, Adrian; Abdel-Aziz, Khaled
Abstract : Case: A 56-year-old Thai lady, with a background of systemic sclerosis/rheumatoid arthritis overlap, presented with new-onset, super-refractory, generalized tonic-clonic status epilepticus requiring intubation and sedation. There was a mild prodromal illness earlier that day. She was loaded with levetiracetam and phenytoin but continued to have seizures during sedation breaks for six days. MRI brain showed medial temporal lobe oedema but no other abnormality. CT chest, abdomen and pelvis was unremarkable. Serum was negative for anti-AMPA1, AMPA2, GABAb-R, VGKC-R, GAD, NMDA-R and onconeural antibodies. CSF analysis was unremarkable apart from the presence of matched oligoclonal bands. Serum anti-glycine receptor antibodies (GlyR-Abs) were strongly positive and the patient received treatment with intravenous methylprednisolone; 1 gram/day for 3 days. The patient entered a remission lasting 11 months (to date) without further immunosuppression. Serum GlyR-Abs titres remained elevated for four months, before normalising. Discussion: GlyR-Abs are typically associated with progressive encephalitis with rigidity and myoclonus (PERM), but have been reported to cause epileptic encephalopathies. Experience with our patient and reports in the literature suggest that GlyR-Abs cause a monophasic epileptic encephalopathy. Based on data from a small number of published cases, it may be possible to induce prolonged remission with pulsed methylprednisolone, without prolonged immunosuppression.